2018
DOI: 10.1038/s41586-018-0635-8
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: A multi-cohort study of the immune factors associated with M. tuberculosis infection outcomes

Abstract: In this Letter, data from 2 out of the 17 progressors were inadvertently binned into the wrong time intervals. We have now re-analysed the entire dataset with all data points binned correctly with respect to the time intervals before tuberculosis (TB) diagnosis, and the first graph in Fig. 4b has been corrected (see Fig. 1 of this Amendment for the original figure). In the revised analysis, the time intervals are set at: >400, 201-400, 101-200 and 0-100 days before TB diagnosis (intervals in the original Fig. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
3
2
0
Order By: Relevance
“…Consistent with these findings, of the 193 Ab features incorporated into the model, 4 of the downselected 5 that were sufficient in discriminating latent and active tuberculosis included Fc or whole but not Fab Ab glycans ( Figure 4B ). Intriguingly, one feature also selected was Ab-mediated induction of CD107a surface expression on NK cells ( Figure 4B ), which is associated with activation and consistent with published literature linking NK cell function to latent tuberculosis in humans [ 5 , 43 ]. Thus, while there is a relative abundance of sialic acid and galactose on Fab domains, Ab glycosylation changes associated with disease resolution occur on the Fc domain and appear to impact Ab functions.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with these findings, of the 193 Ab features incorporated into the model, 4 of the downselected 5 that were sufficient in discriminating latent and active tuberculosis included Fc or whole but not Fab Ab glycans ( Figure 4B ). Intriguingly, one feature also selected was Ab-mediated induction of CD107a surface expression on NK cells ( Figure 4B ), which is associated with activation and consistent with published literature linking NK cell function to latent tuberculosis in humans [ 5 , 43 ]. Thus, while there is a relative abundance of sialic acid and galactose on Fab domains, Ab glycosylation changes associated with disease resolution occur on the Fc domain and appear to impact Ab functions.…”
Section: Discussionsupporting
confidence: 82%
“…This finding was supported by gene expression and GSEA analysis, showing similar representation of B cell genes in active TB patients as compared to LTBI subjects and healthy donors. Thus, our results agree with previous studies reporting unaltered B cell frequencies in the blood of active TB patients and LTBI individuals as compared to healthy controls [ 47 ]. Conversely, other studies have shown significantly decreased or even increased [ 24 , 47 ] B cell frequencies in the peripheral blood of active TB patients [ 23 , 27 , 47 , 48 ] and LTBI [ 47 ] individuals compared to healthy controls.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, our results agree with previous studies reporting unaltered B cell frequencies in the blood of active TB patients and LTBI individuals as compared to healthy controls [ 47 ]. Conversely, other studies have shown significantly decreased or even increased [ 24 , 47 ] B cell frequencies in the peripheral blood of active TB patients [ 23 , 27 , 47 , 48 ] and LTBI [ 47 ] individuals compared to healthy controls. These conflicting data likely reflect differences between study designs and groups of patients enrolled, varying by age, gender, ethnicity, form, and severity of TB disease [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…Data from human and animal models (including NHPs) suggest an important role for diverse lymphocyte populations in controlling Mtb infection. In addition to compelling evidence for the importance of conventional CD4+ and CD8+ T cells (Chen et al, 2009;Foreman et al, 2016;Lin and Flynn, 2015;Lin et al, 2012;Mogues et al, 2001), other lymphocyte populations have been implicated in control including gamma delta (γδ) T cells (Ogongo et al, 2020;Shen et al, 2019), iNKT cells (Arora et al, 2013;Chackerian et al, 2002;Chancellor et al, 2017), donor-unrestricted T cells such as MAITs (Joosten et al, 2019), innate lymphoid cells (ILC) (Ardain et al, 2019) and cytotoxic lymphocytes including NK cells (Lin and Flynn, 2015;Portevin et al, 2012;Roy Chowdhury et al, 2018).…”
Section: T and Nk Cells As Mediators Of Protectionmentioning
confidence: 99%